PENINGKATAN BERAT BADAN BALITA GIZI BURUK YANG MENDAPATPEMBERIAN MAKANAN TAMBAHAN PEMULIHAN DI PUSKESMAS PEKAN LABUHANTAHUN 2013 - Lisparyanda Sihombing; Zulhaida Lubis; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Children under five yearsare group of society that very unstable from nutrition problem. They have a very fast Growth and development in this period so need enough and gratify food and nutrition supply. If malnutrition happens and even severe malnutrition can cause permanent growth and development disturbance physically, mentally, socially, and intelligently that will be brought until adult. If this problem ignored, the worst probability in the next 30 years is lost generation where decreasing human quality in many aspects and will influence productifity so when productifity is low the result is low also. So, to create a better Human Resources quality must begin early that is watch out nutrition status of children of five. This research is observational method by using secunder data from Health center of Pekan Labuhan to learn correlation of Supplementary Feeding Program of Recovery with body weight improvement ofchildren under five that severe malnutrition.According to researched variables, known that there was different body weight of children under five before and after receiving Supplementary Feeding Program of Recovery in Health centre of Pekan Labuhan where all children under five years undergo improvement body weight.During follow Supplementary Feeding Program of Recovery process suggested always given socialitation inorder mothers watch out energy intake of children under five and make sure that they complete PMT-P. Keywords: Supplementary Feeding, Severe Malnutrition, Children UnderFive Years